Zinc enhances autophagic flux and lysosomal function through transcription factor EB activation and V-ATPase assembly - Kim, Ki-Ryeong; Park, Sang Eun; Hong, Ji-Ye; Koh, Jae-Young; Cho, Dong-Hyung; Hwang, Jung Jin; Kim, Yang-Hee (Frontiers in Cellular Neuroscience, 2022)
The stimulation of autophagy or lysosomes has been considered therapeutic for neurodegenerative disorders because the accumulation of misfolded proteins is commonly observed in the brains of individuals with these diseases. Although zinc is known to play critical roles in the functions of lysosomes and autophagy, the mechanism behind this regulatory relationship remains unclear. Therefore, in this study, we examined which mechanism is involved in zinc-mediated activation of autophagy and lysosome. Exposure to zinc at a sub-lethal concentration activated autophagy in a concentration-dependent manner in mRFP-GFP-LC3-expressing H4 glioma cells. Zinc also rescued the blocking of autophagic flux arrested by pharmaceutical de-acidification. Co-treatment with zinc attenuated the chloroquine (CQ)-induced increase in the number and size of mRFP-GFP-LC3 puncta in H4 cells and accumulation of p62 by CQ or ammonium chloride in both H4 and mouse cerebrocortical cultures. Zinc rapidly induced the expression of cathepsin B (CTSB) and cathepsin D (CTSD), representative lysosomal proteases in neurons, which appeared likely to be mediated by transcription factor EB (TFEB). We observed the translocation of TFEB from neurite to nucleus and the dephosphorylation of TFEB by zinc. The addition of cycloheximide, a chemical inhibitor of protein synthesis, inhibited the activity of CTSB and CTSD at 8 h after zinc exposure but not at 1 h, indicating that only late lysosomal activation was dependent on the synthesis of CTSB and CTSD proteins. At the very early time point, the activation of cathepsins was mediated by an increased assembly of V-ATPase on lysosomes and resultant lysosomal acidification. Finally, considering that P301L mutation in tau protein causes frontotemporal dementia through aggressive tau accumulation, we investigated whether zinc reduces the accumulation of protein aggregates in SK-N-BE(2)-C neuroblastoma cells expressing wild-type tau or mutant P301L-tau. Zinc markedly attenuated the levels of phosphorylated tau and total tau as well as p62 in both wild-type and mutant tau-overexpressing cells. We also observed that zinc was more effective than rapamycin at inducing TFEB-dependent CTSB and CTSD expression and V-ATPase-dependent lysosomal acidification and CTSB/CTSD activation. These results suggest that the regulation of zinc homeostasis could be a new approach for developing treatments for neurodegenerative diseases, including Alzheimer’s and Parkinson’s.